KofamKOALA: KEGG Ortholog assignment based on profile HMM and adaptive score threshold - Aramaki, Takuya; Blanc-Mathieu, Romain; Endo, Hisashi; Ohkubo, Koichi; Kanehisa, Minoru; Goto, Susumu; Ogata, Hiroyuki (Bioinformatics, 2020)
Abstract Summary KofamKOALA is a web server to assign KEGG Orthologs (KOs) to protein sequences by homology search against a database of profile hidden Markov models (KOfam) with pre-computed adaptive score thresholds. KofamKOALA is faster than existing KO assignment tools with its accuracy being comparable to the best performing tools. Function annotation by KofamKOALA helps linking genes to KEGG resources such as the KEGG pathway maps and facilitates molecular network reconstruction. Availability and implementation KofamKOALA, KofamScan and KOfam are freely available from GenomeNet (https://www.genome.jp/tools/kofamkoala/). Supplementary information Supplementary data are available at Bioinformatics online.